APPLICATION OF GEOINFORMATION SYSTEMS AT FAST MEDICAL AID: Array - , О. Є. (Municipal economy of cities. Series: «Economy science», 2018)
One of the pressing problems of modern Ukraine is to improve the medical care of the population, in particular in small towns and settlements. Health as a branch of human activity is currently experiencing a period of active informatization. In the conditions of accelerated scientific and technological progress, the introduction of information technologies into various fields of medicine becomes particularly relevant. One of the important aspects of this process is the analysis of the spatial organization of the health care system, the identification of its disadvantages and advantages, the assessment of geographical factors in the process of providing urgent ambulance. Therefore, one of the components of the medical state information system should be the medical geoinformation system, which is designed to solve problems at different levels: regional, regional and local, which creates the preconditions for the formation of different segments of this system. Application of geoinformation technologies and spatial analysis in healthcare relies on a number of areas of knowledge: medical and socio-economic geography, geography of transport and geostation, and many others. A separate task, which can be solved by means of the medical geoinformation system, is the dispatching of ambulances. That is, in our time, the system of providing emergency medical care to the population has become very urgent and of great socioeconomic importance. The system of emergency medical care in our time requires radical changes, as in most post-Soviet settlements, old ambulances are still operating, obsolete equipment is used. And the dispatch system needs a cardinal reorganization. This research is devoted to the issues of creating a geographic information system that could be used to address the issues of dispatching ambulance vehicles and improving the service of the population. To resolve this issue, we propose the creation of one of the most widely used geographic information systems in the world, namely ArcGIS from the American company Esri. With the help of the features of this software, tasks such as registration of patient registration calls, search of the nearest ambulance, search of the shortest path to the patient were solved. Recommendations on the introduction of geoinformation technologies in the healthcare sector are given. That will contribute to improving the quality of life of the population and timely provision of medical services. Keywords: fast medical aid, geoinformation system, shortest path, attribute table.